Management control systemsand stakeholders’ interests in Lithuanian multinational companies: Cases from the telecommunications industry - Jurkštienė, Aušra; Darškuvienė, Valdonė; Dūda, Arūnas (Journal of Business Economics and Management, 2008)
The paper addresses the issue of introduction and effectiveness of modern management control systems (MCS) in Lithuanian enterprises controlled by foreign owners. Modern management control systems are supposed to provide local management with useful information, reflecting firm's performance from different stakeholders’ perspectives. However, the tools of management control sometimes fail in providing with this main function. Thus, the question is raised as to the extent to which performance management systems (PMS) are effective within Lithuanian telecommunication companies, when they are implemented by foreign parent companies in the rapidly changing environment of the industry. The paper reports the findings of a survey of 78 top and middle level managers of two telecommunication companies. Results of the research indicate that differences in the effectiveness of MCS do exist due to the specifics of governance structures within the telecommunication companies. Nevertheless, it is concluded that, when used interactively, a PMS is potentially effective even if a company operates in a rapidly changing environment.First published online: 14 Oct 2010